Tachykinin receptor 3 in the lateral habenula alleviates pain and anxiety comorbidity in mice - Zhang, Wen-Wen; Chen, Teng; Li, Shi-Yi; Wang, Xin-Yue; Liu, Wen-Bo; Wang, Yu-Quan; Mi, Wen-Li; Mao-Ying, Qi-Liang; Wang, Yan-Qing; Chu, Yu-Xia (Frontiers in Immunology, 2023)
The coexistence of chronic pain and anxiety is a common clinical phenomenon. Here, the role of tachykinin receptor 3 (NK3R) in the lateral habenula (LHb) in trigeminal neuralgia and in pain-associated anxiety was systematically investigated. First, electrophysiological recording showed that bilateral LHb neurons are hyperactive in a mouse model of trigeminal neuralgia made by partial transection of the infraorbital nerve (pT-ION). Chemicogenetic activation of bilateral LHb glutamatergic neurons in naive mice induced orofacial allodynia and anxiety-like behaviors, and pharmacological activation of NK3R in the LHb attenuated allodynia and anxiety-like behaviors induced by pT-ION. Electrophysiological recording showed that pharmacological activation of NK3R suppressed the abnormal excitation of LHb neurons. In parallel, pharmacological inhibition of NK3R induced orofacial allodynia and anxiety-like behavior in naive mice. The electrophysiological recording showed that pharmacological inhibition of NK3R activates LHb neurons. Neurokinin B (NKB) is an endogenous high-affinity ligand of NK3R, which binds NK3R and activates it to perform physiological functions, and further neuron projection tracing showed that the front section of the periaqueductal gray (fPAG) projects NKB-positive nerve fibers to the LHb. Optogenetics combined with electrophysiology recordings characterize the functional connections in this fPAG NKB → LHb pathway. In addition, electrophysiological recording showed that NKB-positive neurons in the fPAG were more active than NKB-negative neurons in pT-ION mice. Finally, inhibition of NKB release from the fPAG reversed the analgesic and anxiolytic effects of LHb Tacr3 overexpression in pT-ION mice, indicating that fPAG NKB → LHb regulates orofacial allodynia and pain-induced anxious behaviors. These findings for NK3R suggest the cellular mechanism behind pT-ION in the LHb and suggest that the fPAG NKB → LHb circuit is involved in pain and anxiety comorbidity. This previously unrecognized pathway might provide a potential approach for relieving the pain and anxiety associated with trigeminal neuralgia by targeting NK3R.